Why diets fail (because you're addicted to sugar) : science explains how to end cravings, lose weight, and get healthy - Avena, Nicole M., 1978- (Ten Speed Press, 2014)
"A science-based program and eating plan that helps people cut sugar from their diets, end the cravings that cause most diets to fail, and lose weight permanently"--